2015
DOI: 10.1007/s12149-015-0963-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FDG-PET findings on decisions regarding patient management strategies: a multicenter trial in patients with lung cancer and other types of cancer

Abstract: ObjectiveTo date, numerous studies have been conducted on the diagnostic capabilities of positron emission tomography using [18F]-fluorodeoxyglucose (FDG-PET). However, no studies designed to evaluate the influence of FDG-PET on the selection of patient management strategies within the Japanese healthcare system have been reported to date. The aim of the present study was to investigate prospectively the proportion of patients whose management strategies were modified based on FDG-PET findings (strategy modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…FDG PET/CT is recognized to have a great impact on diagnosing, staging and restaging cancer patients [39][40][41]. Recently, Kubota et al [42] evaluated the impact of FDG PET findings on decisions regarding patient management strategies (i.e., the strategy modification rate) in a prospective multicenter trial in neoplastic patients. The authors reported a strategy modification rate of 71.6 % and 70.0 %, respectively, for patients with lung cancer and malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET/CT is recognized to have a great impact on diagnosing, staging and restaging cancer patients [39][40][41]. Recently, Kubota et al [42] evaluated the impact of FDG PET findings on decisions regarding patient management strategies (i.e., the strategy modification rate) in a prospective multicenter trial in neoplastic patients. The authors reported a strategy modification rate of 71.6 % and 70.0 %, respectively, for patients with lung cancer and malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…22 Kubota et al even showed that PET/CT could contribute to 71.6% of the modifications of management strategies in lung cancer patients. 23 Our data indicated that clinical stage I lung cancer patients who received PET/CT had a higher lobectomy rate and a lower wedge resection rate. Moreover, patients were more likely to receive chemotherapy after receiving PET/CT.…”
Section: Discussionmentioning
confidence: 59%
“…In fact, modifications in tumor glucose metabolism occur earlier than those in tumor size, thus resulting useful in differentiating persistent disease from scar tissue. 24,25 In our study, we investigated whether 18F-FDG PET/CT parameters, at baseline and after induction therapy, were useful to assess the response to chemotherapy and to predict outcomes in patients with stage III NSCLC, which still represents a challenge for clinicians. In particular, we studied metabolic parameters derived from primary tumor and regional lymph nodes separately.…”
Section: Discussionmentioning
confidence: 99%